Pengaruh Implementasi Syariah Governance Dan Reputasi Terhadap Minat Nasabah Menggunakan Produk Tabungan Emas Di PT. Pegadaian (Persero) UPS Madina: Azizah Anna Sahra - Azizah Anna Sahra (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2026)
The purpose of this study is to see and analyze how much influence the Implementation of Sharia Governance has on Customer Interest in using gold savings products, to see and analyze how much influence Reputation has on Customer Interest in using gold savings products, and to see and analyze how much influence the Implementation of Sharia Governance and Reputation has on Customer Interest in using gold savings products. This research is a quantitative research with data collection techniques using questionnaires (surveys) with a total of 40 respondents using the Accidental Sampling technique with the help of SPSS 2025. Based on the results of the research conducted, the Implementation of Sharia Governance (X1) has a positive effect on Customer Interest (Y) with a significant level of (0.000 t table (2.368>1.685) with a significant level of 0.05, and Reputation (X2) has a significant effect on Customer Interest (Y) with a significant level of (0.000 t table (2.339>1.685).), and the Implementation of Sharia Governance (X1) and Reputation (X2) have a significant effect simultaneously on Customer Interest (Y) with a significant level of (0.000f table (17,332 > 3,25), and the R Square value is 0.356 or 35.6%, which means that variables X1 and X2 (Sharia Governance and Reputation) can influence variable Y (Customer Interest) by 35. 35.6% and the remaining 64.4% is influenced by other factors not discussed in this study. Keywords: Implementation of Sharia Governance, Reputation, and Interest